2011
DOI: 10.1007/s12011-011-9161-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Phosphate Fertilizer Application on the Heavy Metal Content in Agricultural Soils with Different Cultivation Patterns

Abstract: The use of phosphate fertilizers is essential in agriculture, because they supply farmland with nutrients for growing plants. However, heavy metals might be included as impurities in natural materials and minerals, so heavy metals can also be present in phosphate fertilizers or other chemical fertilizers. The aim of this work was to assess the heavy metal content and contamination status of agricultural soils in the Hamadan province of Iran used for the cultivation of different crops, including cucumber, potat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 27 publications
3
25
0
1
Order By: Relevance
“…Apart from atmospheric deposition the largest contribution of cadmium to English and Welsh agricultural soils is inorganic fertilisers, specifically phosphate fertilisers (Nicholson et al, 2003).The long term application of these fertilisers could potentially have led to an accumulation of heavy metals in the soil (Cheraghi et al 2012). It has been observed that the long term use of phosphate fertiliser led to a moderate accumulation of some heavy metals (including lead) and a significant accumulation of cadmium in the soils of Hamadan province in Iran (Cheraghi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from atmospheric deposition the largest contribution of cadmium to English and Welsh agricultural soils is inorganic fertilisers, specifically phosphate fertilisers (Nicholson et al, 2003).The long term application of these fertilisers could potentially have led to an accumulation of heavy metals in the soil (Cheraghi et al 2012). It has been observed that the long term use of phosphate fertiliser led to a moderate accumulation of some heavy metals (including lead) and a significant accumulation of cadmium in the soils of Hamadan province in Iran (Cheraghi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The principal Mn depletion mechanisms are uptake by crop plants, loss through soil erosion, leaching, and adsorption on organic compounds or microbial biomass (Cheraghi et al, 2012;Geissen et al, 2010). The major anthropogenic sources of Mn are municipal wastewaters, sewage sludge, and metal smelting processes (Hu et al, 2009;Ning et al, 2010).…”
Section: B Manganesementioning
confidence: 99%
“…Atafar et al (2010) obtuvieron resultados similares en un estudio sobre el efecto de fertilizantes en suelos de la provincia de Kermanshash, Irán, en el cual reportaron que los fertilizantes compuestos y triple super-fosfato contenían la mayor concentración de Cd; para el Pb y As la concentración máxima se encontró en un fertilizante a base de sulfato de zinc, reportando que las concentraciones de Cd, Pb y As aumentaron en los suelos después de la aplicación de estos fertilizantes. Cheraghi et al (2012) coincidieron en que los fertilizantes a base de fosfato son fuente importante de MP ya que la materia prima de estos productos se obtiene de depósitos de fosforita que, en general, contienen altas concentraciones de Cu, Cd, Ni, Zn, Co, Pb y Mn. En el mismo sentido, es importante mencionar que algunos productos comerciales recomendados para el cultivo de caña reportan en su ficha técnica que contienen los siguientes MP: Al, Cd, Cu, Fe, Mg, Mn, Ni, Pb, Zn y As (Palau-Bioquim, s.f.…”
Section: Distribución De Mp En Suelos Y Sedimentosunclassified